Glyphosate-resistant Kochia (Kochia scoparia) management in the central Great Plains and western Canada - Westra, Eric P., author; Nissen, Scott, advisor; Kniss, Andrew, advisor; Olson, Brian, committee member; Shaner, Dale, committee member; Barbarick, Ken, committee member (Colorado State University. Libraries, 2016)
Glyphosate-resistant (GR) kochia (kochia scoparia) has become more common throughout the Western Great Plains, and has now been reported to exist as far south as Texas up to Canada. Further evolution of GR kochia threatens the utility of glyphosate and GR crops for weed control, therefore, research relating to the management of GR kochia was conducted to address this current widespread problem. First, a four year survey study was conducted across Eastern Colorado to determine the frequency and occurrence of GR kochia in Eastern Colorado. Each year, kochia seed was collected from geo-referenced sites across Eastern Colorado for greenhouse screening to evaluate resistance to glyphosate, dicamba, and fluroxypyr. Over the four years, the occurrence of GR kochia remained fairly constant with 60, 45, 39, and 52% of populations tested categorized as GR. The same was observed for dicamba-resistant kochia over the three years with 33, 45, and 28% of populations tested categorized as dicamba-resistant. For the three years tested, no collections were deemed resistant to fluroxypyr. Populations with multiple resistance to glyphosate and dicamba increased over the three years with 14, 15, and 20% of the populations classified as resistant to both glyphosate and dicamba, which highlights the importance of fluroxypyr for control of these multiple resistant populations. Unlike resistance to acetolactate synthase (ALS), or Acetyl-CoA carboxylase (ACCase) inhibitor herbicides, the rate of evolution for glyphosate or dicamba resistant kochia appears to be slower at the landscape level which suggests there may be a potential fitness penalty or inheritance restriction keeping the frequency and occurrence of resistance fairly stable over the four years. Next, field studies were conducted to evaluate how treatments influence the further selection of GR kochia when starting at a targeted baseline of 10% GR kochia. For POST treatments, glyphosate was compared to glufosinate, and the inclusion of a pre-emergent herbicide (pendimethalin) with both glyphosate and glufosinate was evaluated to determine how herbicide treatments impact the further selection of GR kochia progeny. The impact of canola variety selecting for GR in the absence of herbicide applications was compared between DKL 30-42 and InVigor L150. Kochia survivors from treatments with glyphosate had progeny with higher frequencies of GR compared to kochia survivors from treatments with glufosinate. However, the advantage of reducing the frequency of GR progeny from treatments with glufosinate was reduced when the control efficacy of glufosinate decreased in the second year. The inclusion of a pre-emergent herbicide (pendimethalin) reduced the frequency of GR kochia progeny and significantly reduced the number of kochia individuals that were exposed to post-emergent applications, which is key for GR kochia management. Canola variety did contribute to kochia suppression, but both varieties appeared equivalent in their suppression, however differences in phenotypes between canola varieties impacted the frequency of GR kochia progeny that remained below the canola canopy. Management recommendations to minimize further selection and evolution of GR kochia in Canola are to incorporate an alternative mode of action (glufosinate) either in a rotation or tank mix (once varieties are available) to reduce the frequency of GR kochia progeny, and most importantly, to incorporate a pre-emergent herbicide to limit the further selection and evolution of GR kochia.
Keywords: fluroxypyr; herbicide resistance; survey; glyphosate; dicamba; Kochia scoparia